The extent to which King Abdulaziz University students are aware of the concept and practice of digital citizenship - Almalki, Nawaf Abdulmajeed (Journal of Humanities & Social Sciences, 2021)
The study aimed to get to know the extent of consciousness students of the Faculty of Communication and Media at the university understands the concept and importance of digital citizenship. As well as learning about the methods of practicing digital citizenship from the viewpoint of students of the Faculty of Communication and Media at King Abdulaziz University. The study used the quantitative approach and the descriptive analytical approach. The study population consisted of (84) male and female students from the Faculty of Communication and Media at King Abdulaziz University. The questionnaire was used as a study tool, the validity and reliability of the questionnaire were verified and the data collected and analyzed by appropriate statistical methods using the SPSS program. Among the most important findings of the study: The level of awareness of students of the Faculty of Communication and Media at King Abdulaziz University was high, and the degree of practicing its methods was high as well. The study recommended that attention should be paid to developing university students ’awareness of the concept of digital citizenship through educational seminars and workshops, and integrating digital citizenship into school curricula, and training of faculty members in the methods of practicing digital citizenship.